Psychology, Learning, Technology First International Conference, PLT 2022, Foggia, Italy, January 19-21, 2022, Revised Selected Papers - Limone, Pierpaolo; Di Fuccio, Raffaele; Toto, Giusi Antonia (Communications in Computer and Information Science, 2022)
This open access book constitutes the refereed proceedings of 1st International Workshop on Psychology, Learning, Technology, PLT 2022, Foggia, Italy, during January 2022. The 8 full papers presented here were carefully reviewed and selected from 23 submissions. In addition, one invited paper is also included. Psychology, Learning, ad Technology Conference (PLT2022) aims to explore learning paths that incorporate digital technologies in innovative and transformative ways and the improvement of the psychological and relational life. The conference includes topics about the methodology of application of the ICT tools in psychology and education: from blended learning to the application of artificial intelligence in education; from the teaching, learning, and assessment strategies and practices to the new frontiers on Human-Computer Interaction.